Pathomorphological Study of Coronary Atherosclerosis in Deceased Patients - Halina Pérez Álvarez; José Fernández-Brito Rodríguez (Revista Finlay, 2022)
Background: atherosclerosis is a disease of the general metabolism, with damage to the vascular endothelium, which has led to multiple researches using the atherometric system. Objective: to characterize and compare the atherosclerotic lesion with the use of the atherometric system in the coronary arteries of deceased patients with medico-legal autopsies according to age group. Methods: an applied, descriptive, longitudinal and prospective research was carried out. The universe consisted of 183 autopsies, consecutively from the Institute of Legal Medicine, from 2018 to 2019 and the population of 108 deceased divided by age groups. The operationalized variables were the main arterial sectors that supply the heart. The atherometric system was applied to the right and left coronary arteries in their anterior descending and circumflex branches. Results: fatty streaks were found in all the arteries of those less than 20 years of age, fibrous plaque in the right coronary artery and anterior descending artery in those between 21 and 40 years of age, and severe plaque in the group between 41 and 60 years of age. Arithmetic means and standard deviations increased with age for all variables. There was a correlation of fatty streaks between the three arteries in the group from 21 to 40, in the group from 41 to 60 between the right coronary artery and the circumflex artery, and a marked correlation between the circumflex artery and the anterior descending artery for fibrous plaques in the group from 41 to 60 years old. 60 years. Conclusions: the atherosclerotic lesion was present in the three arteries, the total number of atherosclerosis increased with age, with fibrous plaques appearing from the second decade of life, severe plaques were not observed before the age of 40, and the use of atherometric system turned out to be a useful tool for the study of atherosclerosis.